Przywództwo dyrektora szkoły a zmiana i uczenie się nauczycieli we wspólnotach praktyków = The headmaster`s leadership in view of change and of teacher learning in communities of practice - Madalińska-Michalak, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper focuses on the issue of the headmaster?s leadership, change, and learning at school. The main research questions concern the role of headmasters in teacher learning and their leadership in the course of changes taking place at school. Prior to answering these questions, the author reflects upon the essence of social learning and change at school. These considerations are based on Etienne Wenger?s model of social learning in communities of practice and Michael Schratz` model of change and learning.
Keywords: przywództwo edukacyjne; dyrektor szkoły; uczenie się; wspólnoty praktyków; zmiana w szkole; educational leadership; headmaster; learning; communities of practice; change at school